Guía para el desarrollo de la psicomotricidad de los niños/as de 3 a 4 años a través del juego - Heredia Flores, Blanca Isolina (2015)
This research was conducted at the private school "Rousseau" located in Canton parish Cayambe Ayora on the subject: Guidelines for the development of coarse psicomotridad of children from 3 to 4 years through play, thinking younger students have since noticed that children of this age have little stimulation in the large motor development due to ignorance of techniques by teachers and parents, which does not allow learning in children occurs properly. Gross motor skills is essential in early childhood because that is where the child / to begin discovering the movement of his body, and later to move independently through the game that has a transcendent meaning in life children not only playful but also cognitive, personal and social education of children / as. It also helps the child to express themselves freely develop their imagination and also create your identity, autonomy and strengthen coexistence with others in their environment. The five years of his childhood the child has the characteristics that the mind develops and stay alert and curious, while the body remains energized for rapid movements such as crawling, running, jumping, hopping, crawling hence it is considered that the body of the child must be continuously active for: learn, play and grow.